Comparisonal Analysis Of D35 Bulldozer And GD300A-1 Motor Grader As A Grade Tool Reviewing From Time - Nur Azizah (Journal of Science Nusantara, 2022)
In the sub work of the Nglinggis access road, there is a work of embankment of soil fromselected local materials. This work includes taking material from the stock pile, transporting itto the site, leveling the soil and compacting the soil. Soil leveling in this project uses BulldozerD35 as a leveling tool. In doing land leveling work there is another method that can be used,namely the method of heavy equipment in the form of a Motor Grader. In the condition of theland for the Nglinggis access road, the type that is suitable for use is the Motor Grader GD 300A-1. The use of heavy equipment can affect the estimated time on a job. Therefore, the selectionof an efficient tool for the job is very important. From the specifications, the speed of the GD300 A-1 Motor Grader is superior to the D35 Bulldozer. The purpose of this study is to analyzethe comparison between Motor Grader and Bulldozer as a leveling tool, it can be seen whichtool is the most efficient if used as a leveling tool in earthworks at the Nglinggis Access RoadWorks at the Tugu Dam Spillway Construction Project, Kab. Trenggalek. The results showedthat based on the average waiting time, the Bulldozer D35 was 0.31 minutes faster than theMotor Grader GD 300 A-1 in each cycle. And based on time weighted average, the BulldozerD35 is 0.03 minutes faster than the Motor Grader GD 300 A-1 on each cycle.